The Effect of Yoga on the Intensity of Primary Dysmenorrhea in Adolescent Girls at Insan Permai Youth Posyandu Cikancung Village Bandung - Nanik Cahyati; Fitri Nurhayati; Nenden Sumarlina (Institute of Computer Science (IOCS), 2022)
Dysmenorrhea is pain during menstruation that interferes with the daily activities of adolescent girls such as decreased concentration on learning because of the pain felt. One way to reduce the intensity of dysmenorrhea is with yoga. Therefore, it is necessary to prove the effect of yoga on dysmenorrhea intensity. The general purpose of this study was to determine the effect of yoga on the intensity of dysmenorrhea in adolescent girls at the Insan Permai Youth Posyandu, Cikancung Village. While the specific purpose is to identify the dysmenorrhea intensity score before and after yoga and analyze the effect of yoga in reducing dysmenorrhea in adolescent girls at the Insan Permai Youth Posyandu, Cikancung Village, Bandung Regency. This research design is a quantitative analytic pre-experiment with a one group pretest-posttest design approach and calculated using the paired t-test. The sample in this study amounted to 25 adolescent girls with data collection tools in the form of NRS (Numeric Rating Scale) observation sheets. The results of the study obtained a dysmenorrhea intensity scale before yoga with a mean of 4.32 and a dysmenorrhea intensity scale after yoga with a mean of 2.08 and p-value <0.05. This means that there is an effect of yoga in reducing dysmenorrhea in adolescent girls. This research is expected to be a reference for young women in reducing dysmenorrhea and midwives can also provide promotion that yoga is an alternative way to overcome dysmenorrhea.